تطبيق طريقة “Hipnoteaching” في تعليم مهارة الكلام - Junaedi; Hanifah, Umi; Abidin, Nur; Mumtaza, Shofia; Salsabila, Putri (Prosiding Konferensi Nasional Bahasa Arab dan Pembelajarannya di Era Milenial, 2022)
The hypnoteaching method is a learning method in which the teacher uses subliminal languages that can foster interest in students. This study aims to describe of the Application of the Hypnoteaching Method in the learning process of speaking skills. This research is quantitative. The result of this study is the implementation of the Hypnoteaching Method is effective in the application of speaking-skill learning.